Estudo físico-químico de kombucha com pólen - Silva, Julia Teodoro da (2025)
In this study, kombucha with green tea and bee pollen was prepared in order to obtain a functional drink rich in bioactive compounds. The analyzes were carried out on the samples of the first FI fermentation (0, 4, 6, 8 and 10 days) without pollen and in the second FII fermentation (+10 days in a closed bottle), with and without pollen. Total phenolic compounds were determined using the Folin-Ciocaulteau method. In times zero and 10 days of IF, the concentration of total phenolic compounds ranged from 96.61 to 134.74 mg AG L-1, the pH from 3.71 to 3.18, the °BRIX from 5.90 to 4.60, the protein content from 81.754 to 85.357 mg L-1, acidity in acetic acid from 0.08 to 0.22 g 100mL-1 and the reducing sugars from 0.095 to 0.162 g 100mL-1. In kombucha after the end of FII without and with pollen, the concentration of total phenolic compounds was equal to 159.74 and 289.60 mg AG L-1, pH 3.09 and 3.05, the °BRIX 4.60 and 2.15, proteins 21.357 and 83.421 mg L-1, acidity in acetic acid 0.24 and 0.35 g 100mL-1 and, the content of reducing sugars was 0.28 and 0.27 g 100mL-1, respectively. The concentration of total phenolic compounds in fermented pollen increased in relation to pure pollen from 393.03 mg AG L-1 to 653.74 mg AG L-1. In protein analysis, pure pollen contains 17% of proteins in 200 mg, while fermented dry pollen in Fll has 25% of proteins in 200 mg. It was found that during the FI and FII fermentation process there was an increase in acidity and decrease in pH and °BRIX, indicating the consumption of sucrose and production of organic acids. The concentration of phenolic compounds increased during the course of IF and FII, mainly with the addition of bee pollen. Kombucha proved to be efficient in pollen fermentation, increasing the availability of antioxidant compounds present in pollen.